A big, spooky house - Washington, Donna L., 1967- (Jump at the Sun/Hyperion Books for Children, 2000)
On his way to join the army, the big strong man of the village, who is scared of nothing, spends the night in a spooky house where a series of ever-larger cats ask him the same unusual question.